Performance of a pharmaceutical services regionalization strategy policy in Minas Gerais, Brazil: Pre-post analysis from ERAF project - Tatiana Chama Borges Luz; Tatiana Chama Borges Luz; Ana Karine Sarvel de Castro; Isabela Cristina Marques; Betania Barros Cota; Jèssica de Castro Alves; Michael Robert Law (Frontiers Media S.A., 2022)
Background: In 2016, the Brazilian state of Minas Gerais (∼20 million people), implemented the ERAF policy ("Regionalization Strategy of Pharmaceutical Services") in an effort to improve medicine procurement and distribution within primary care. We evaluated the impact of the policy on three main goals: price reductions, volume increases, and expansion of therapeutic options.Methods: We analyzed the procurement data from the Integrated System of Management of Pharmaceutical Services database in 2012 and 2018. We estimated the volume, drug mix, and expenditure indicators for all major therapeutic classes, and, in detail, for cardiovascular and nervous system drugs. We evaluated the expenditure drivers using decomposition analyses.Results: Overall, the expenditure increased by 14.5%, drug mix almost doubled, while the volume decreased by a third. Cardiovascular and neurological system drugs followed similar patterns. Decomposition analyses showed that prices and drug mix had positive effects while the volume had negative effects, resulting in an overall increase in expenditure.Conclusion: Our findings suggest that the ERAF policy cannot be considered effective as it has not fulfilled its intended purposes so far. Strategies to address the identified problems and to build a platform for a more sustainable long-lasting policy should be put in place by the government.